A short review on identification of ABCDE genes in monocot plants: Short review of ABCDE genes in monocot plants - Suchilkumar Soorya; Thacheril Sukumaran Swapna; Kalluvettankuzhy Krishnan Nair Sabu (Journal of Tropical Life Science, 2022)
One of the most important divisions in the plant kingdom is the monocotyledon division of angiosperms. More than 60,000 monocot spp. have been identified, the majority of which are economically important, such as the Poaceae, Orchidaceae, Arecaceae, Liliaceae, and certain other families. The involvement of the ABCDE model of floral organ determination during flower development is a growing area of research in the field of molecular biology due to the diversity in the floral morphology of monocots. The MADS-box gene family is a large molecular transcript family that helps identify specific proteins involved in floral development. It is classified into several classes based on its function. The review aimed to evaluate the significance of Â ABCDE genes for floral development and subsequent organ identification, which have been discovered in a range of monocot plants, as well as the functions of these genes in determining the sex of dioecious plants. We sought to summarise the MADS-box gene responsible for flower initiation and floral whorl differentiation reported in economically valuable monocotyledonous plants.